Poéticas de la violencia en Colombia. El papel de la poesía en la formación de una memoria crítica (2018)
The objective of this research article is to analytically address a poetry corpus in regards to Colombian poetry between 1940 and the first decade of the XXI century. This is done with the purpose of determining the role of poetry in the formation of critical citizen memory.A first state of the art is put forward. That is, a recent study of the poetry of violence in Colombia is addressed within the period already mentioned through a document analysis in books and analogous and database journals.Through this analysis and study, I stablished that lyrical discourse shapes and gives voice to a specific period in Colombian cultural, social, economic and political life. This is due to how poetry shows different forms of violence that this country suffered during the twentieth century when republican life is enforced. Likewise, according to novelist Thomas Mann, an artist, like poets, are viewed not as a moral being but an esthetic human being whose fundamental instinct is game and not virtue. That is why, Mann, in all his ingenuity, allows himself to play dialectically through questions and antinomies of morality and exempts himself from being judged when he questioned the absurdity of human condition in his poems. Thus, literary art is built as a pertinent discourse for the development of critical thinking and the constitution of an ethical and moral memory.